Adjuvant Chemotherapy and Vaginal Vault Brachytherapy With or Without Pelvic Radiotherapy for Stage 1 Papillary Serous or Clear Cell Endometrial Cancer. Issue 2 (1st February 2016) - Tétreault-Laflamme, Audrey; Nguyen-Huynh, Thu Van; Carrier, Jean-François; Samouëlian, Vanessa; Sauthier, Philippe; Beauchemin, Marie-Claude; Barkati, Maroie
Abstract : Objective: The aim of this study was to assess and compare adjuvant chemotherapy followed by either high–dose-rate vaginal vault brachytherapy (VBT) alone or combined with pelvic external beam radiotherapy (EBRT) for International Federation of Gynaecology and Obstetrics stage 1 serous or clear cell (CC) endometrial cancer. Methods: Between 2006 and 2012, 84 women with stage 1 serous or CC endometrial cancer were evaluated postoperatively for adjuvant treatment at our hospital. More than 80% of patients had pelvic lymphadenectomy. Patients declining or not completing adjuvant treatments were excluded. Twenty-five women received 4 to 6 cycles of carboplatin/paclitaxel followed by EBRT and VBT. Thirty-two women received 6 cycles of carboplatin/paclitaxel followed by VBT. Locoregional control and toxicities were assessed during follow-up. Results: The 3-year disease-free survival and overall survival rates for the VBT group compared with the EBRT + VBT group were 88% versus 84%, P = 0.6, and 100% versus 94%, P = 0.6, respectively. Only 1 patient in the EBRT + VBT group developed a distant recurrence. One patient had grade 3 toxicity (chronic gastrointestinal [GI] toxicity) in the EBRT + VBT group. Acute grade 1-to-2 GI and grade 1 genitourinary (GU) toxicities were less frequent in the VBT group compared with the EBRT + VBT group ( P = 0.008 and P = 0.019, respectively). Late GI and GU toxicities were comparable. Grade 1 vaginal toxicity was similar in both groups. No acute or late grade 2 GU or vaginal toxicities were reported. Conclusions: According to this study, VBT alone seems to be as effective as EBRT and VBT for stage 1 serous and CC endometrial cancer treated with surgery and adjuvant chemotherapy. Furthermore, less acute GI and GU toxicities were seen in the VBT group.